The Use of Pragmatic Politeness Theory in the Interpretation of Hemingway's "Hills like White Elephants" - Enrique Lafuente Millán (Miscelánea: A Journal of English and American Studies)
In the interpretation of a literary text, specially if the information granted by the author is insufficient, reinterpretation by means of inferences is necessary. The reader's previous background knowledge will often position him/ her in his/ her interpretation and so the text is open to subjective rendering. I we accept that literary dialogue is another form of social communication, Pragmatic Theory can be of help when it comes to studying texts like “Hills like White Elephants”, where the words uttered by the characters hold the key to the meaning of the story. In this article, I will mainly use Brown and Levinson's politeness theory to analyze the strategies used by the two interactants in an attempt to-sketch a profile of the motivations underlying their linguistic behaviour and to provide a less arbitrary interpretation of the text.